Impact of Eyes and Visual Functions in Safe Driving (Janaki Medical College Journal of Medical Science, 2021)
Driving is a high level of visual functions demanding occupation. The relationship of good visual function and driving safety are innately and unarguably linked and have a direct bearing on the incidence of road traffic accidents. A more practical approach to improve the efficacy of vision screening at licensure is to examine visual acuity screening test supplemented by other types of screening tests like contrast sensitivity, visual field, binocularity, color vision, processing speed, light and dark adaptation etc. These clinical tests have a large evidence basis for their relevance to driver safety and should be mandatory for obtaining and renewing the driving license. The individual who failed the initial screening should undergo a protocol based comprehensive evaluation by an Ophthalmologist or Optometrist if fit to drive in future. Visual acuity and other visual functions requirements for driving vary from country to country though most countries mandate visual acuity of 20/40 in the better eye with horizontal visual field of 120 degrees. But there is variation regarding provision of color vision, binocularity, contrast sensitivity and night vision tests. Nepal yet , has not strict rules regarding evaluation of visual functions for safe driving. But indeed, a local expert review board should determine the suitability to issue a normal driving license or a restricted driving license, a temporary or a permanent denial for those who partially or completely failed the vision specific requirements. Moreover appropriate modification of the existing laws and expedited implementation are mandatory to minimize visual functions related road traffic accidents which is an avoidable cause of mortality and morbidity.